Development of BPM Capabilities - Is Maturity the Right Path? - Plattfaut, Ralf; Niehaves, Björn; Pöppelbuß, Jens; Becker, Jörg (19th European Conference on Information Systems (ECIS), 2011)
Business Process Management (BPM) is an influential concept in information systems (IS) research and management practice. While a great number of studies dealt with developing methods, procedures, or tools for BPM, especially process modeling, today the question of how to assess and – from that point on – to develop BPM capabilities in a real-life organization has become key to BPM practice and is becoming a central element in BPM research as well. A plethora of BPM maturity models have been designed for the purpose of guiding the development of BPM capabilities in organizations. In this study, we take a critical perspective on maturity models for BPM capability development and present a case study example where maturity model-based guidance is rendered to be inadequate if not further considering organizational position and environment. Our theory discussion introduces alternative takes on BPM capability development, lays out implications for BPM practice, and presents potentially fruitful paths for future research and theory in the area of BPM capability development.